2008
DOI: 10.1577/m07-043.1
|View full text |Cite
|
Sign up to set email alerts
|

Aquatic Macrophyte Encroachment in Chinook Salmon Spawning Beds: Lessons Learned from Gravel Enhancement Monitoring in the Lower Mokelumne River, California

Abstract: We studied the effects of colonization of the spawning habitat of Chinook salmon Oncorhynchus tshawytscha by rooted aquatic macrophytes in a regulated central California river. At least seven species of plants invaded four spawning sites below the lowest nonpassable dam during an extended period of relatively low instream flows. The depths associated with aquatic vegetation were similar to those used by spawning salmon. Velocities were significantly lower where plants took root. As plants expanded over riffles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Consequently, many agencies tasked with restoring populations have attempted to enhance spawning potential by reconfiguring entire channels and/or depositing sediments considered favourable for reproductive adults and incubating eggs (Kondolf et al. 1996; Kondolf 2000; Merz et al. 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, many agencies tasked with restoring populations have attempted to enhance spawning potential by reconfiguring entire channels and/or depositing sediments considered favourable for reproductive adults and incubating eggs (Kondolf et al. 1996; Kondolf 2000; Merz et al. 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Spawning habitat degradation in natal rivers induced by hydraulic mining, dams and water diversion is believed to be a principle impediment to salmon recovery (Yoshiyama et al 1998(Yoshiyama et al , 2000Zeug et al 2011). Consequently, many agencies tasked with restoring populations have attempted to enhance spawning potential by reconfiguring entire channels and/or depositing sediments considered favourable for reproductive adults and incubating eggs (Kondolf et al 1996;Kondolf 2000;Merz et al 2008). The quality of such engineered habitat for juveniles rearing in their natal rivers remains largely unknown, yet elucidating the effects of large-scale spawning habitat remediation on juvenile salmon rearing conditions is necessary to gauge the value of such management actions holistically, as parr growth rates may influence survival during later life stages (Quinn & Peterson 1996;Moss et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Sudden collapses remain unexplained but have been observed throughout Europe (Simberloff and Gibbons 2004;Mjelde et al 2012). In regulated rivers in its native range, Elodea has been found to encroach on spawning sites of Chinook salmon (Oncorhynchus tshawytscha) (Merz et al 2008).…”
Section: Elodea Ecology Management and History In Alaskamentioning
confidence: 99%
“…The logistic growth model differs from commonly used population models like the Ricker model in how it describes population change at very high population densities (Ricker 1975). In the logistic growth model, growth at very high densities declines more rapidly, an assumption supported by the encroachment effects of Elodea observed on spawning adult salmon (Merz et al 2008). In addition, the limiting environmental conditions of Elodea's encroachment into salmon spawning beds is captured by the harvest limitation (K) in the logistic model but is lacking in an exponential growth model.…”
Section: Bioeconomic Modelmentioning
confidence: 99%
“…For example, Haxton et al [16] found that the relative abundance of lake sturgeon was lower in regulated rivers than in unregulated rivers in Ontario. Low flows resulting from dam construction in California were found to increase the growth of aquatic plants and thereby decrease Chinook salmon spawning habitat availability [17]. Fish abundance, demographic parameters, and diversity were found to consistently decline in response to both increases and decreases in flow magnitude (reviewed in Poff and Zimmerman [13] but also see Webb et al [18]).…”
Section: Introductionmentioning
confidence: 99%